Fazlur Rahman and the Reconstruction of Islamic Thought; The Role of Ijtihad and the Relevance of the Qur'an in the Context of Religious Moderation - Alfiyan Yusuf Maulana; Shofiyullah MZ (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines Fazlur Rahman's thoughts on the reconstruction of Islamic thought, focusing on the role of ijtihad and the relevance of the Qur'an in the context of religious moderation in Indonesia. Rahman emphasizes the importance of ijtihad as a critical method in understanding sacred texts, which allows for the adaptation of Islamic teachings to social dynamics and the challenges of the times. He argues that a contextual understanding of the Qur'an can produce interpretations that are more relevant and applicable to contemporary society. By exploring key concepts in his thought, this article aims to demonstrate how Rahman's approach can provide solutions to problems faced by Muslims in the modern era, as well as inspire dialogue between tradition and innovation in Islamic studies. The method used in this study is a library research method, taking primary references as the main foundation and secondary references as supporting sources. Through this perspective, the reconstruction of Islamic thought is not only a necessity or discourse, but also an opportunity to strengthen the values ​​of justice, humanity, and sustainability in an Islamic society.